Analysis of Phonological Errors in Banners on Jalan Siliwangi - Hana Nurhasanah; Meydita Hidayat; Ira Waridah; Ai Siti Nurja Milah (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
Talking is an activity that cannot be separated from the interaction between people in daily life, starting from oral to written. In written language, there are many linguistic errors, both in terms of phonemes, morphemes, and word writing. This study aims to analyze and describe language errors in external media located on Siliwangi Street, Tasikmalaya. Qualitative descriptive is a method used in this study by grouping data, analyzing data, and drawing conclusions based on the results of the analysis. From this study, it was obtained that the phoneme replacement error was found in the replacement of the phoneme /ai/ with /e/, /u/ with /o/, and /r/ with /e/, the phoneme deletion error was found in the deletion of the phonemes /s/, /n/, and /k/, and the errors in the replacement and addition of phonemes were found in the replacement of the phoneme /o/ to /o/, the replacement of the phoneme /g/ with /k/ and the addition of the phoneme /e/.